Voices from the pandemic : Americans tell their stories of crisis, courage and resilience - Saslow, Eli (Doubleday, 2021)
"From Pulitzer Prize-winning Washington Post reporter Eli Saslow, a powerful portrait of a country grappling with the pandemic, told through voices of people from all across America The Covid-19 pandemic was a world-shattering event, affecting everyone in the nation. From its first ominous stirrings, renowned journalist Eli Saslow began interviewing a cross-section of Americans, capturing their experiences in real time: An exhausted and anguished EMT risking his life in New York City; a grocery store owner feeding his neighborhood for free in locked-down New Orleans; an overwhelmed coroner in Georgia; a Maryland restaurateur forced to close his family business after forty-six years; an Arizona teacher wrestling with her fears and her obligations to her students; rural citizens adamant that the whole thing is a hoax, and retail workers attacked for asking people to wear masks; patients struggling to breathe and doctors desperately trying to save them. Through Saslow's masterful, empathetic interviewing, we are given a kaleidoscopic picture of a people dealing with the unimaginable. These deeply personal accounts make for cathartic reading, as we see Americans at their worst, and at their resilient best"--